Kepemimpinan Siti Walidah dalam pendidikan - Alfaien, Noor Isna; Vashti, Respati Prajna (Ta’dibuna: Jurnal Pendidikan Islam, 2022)
The leadership model of a leader will determine what steps must be taken to achieve educational goals. To achieve educational goals, a person must have a leadership spirit. Siti Walidah, who is also better known as "Nyai Ahmad Dahlan" is one of the leaders in the formation of the "Aisiyah" organization. Through her role as Nyai Ahmad Dahlan, she took this opportunity to fight, by providing opportunities for women to get an education. This research was conducted to know the Islamic education leadership model from the perspective of Siti Walidah. The hope is that Siti Walidah’s leadership model produces a leadership style in Islamic education, of course, this leadership style can be used as a reference when a woman becomes a leader in an educational organization. This research is included in the type of library research, by reading, analyzing, and concluding the relevant literature. There are two leadership models that Siti Walidah uses in building educational organizations, including transformational leadership and visionary leadership. Abstrak Model kepemimpinan seorang pemimpin akan menentukan langkah apa yang harus dilakukan untuk mencapai tujuan pendidikan. Untuk mencapai tujuan pendidikan seseorang harus memiliki jiwa kepemimpinan. Siti Walidah sosok yang juga lebih terkenal dengan panggilan "Nyai Ahmad Dahlan” merupakan salah satu pemimpin dalam pembentukan organisasi "Aisiyah”. Melalui perannya sebagai Nyai Ahmad Dahlan, di ambilnya kesempatan ini untuk memperjuangkan, dengan memberikan kesempatan kepada para perempuan dalam mendapatkan pendidikan. Penelitian ini dilakukan dengan tujuan untuk mengetahui model kepemimpinan pendidikan Islam perspektif Siti Walidah. Harapannya adalah model kepemimpinan Siti Walidah menghasilkan gaya kepemimpinan dalam pendidikan Islam, tentu gaya kepemimpinan ini dapat dijadikan sebagai acuan ketika seorang perempuan menjadi pemimpin dalam suatu organisasi pendidikan. Penelitian ini termasuk dalam jenis penelitian kajian pustaka (library reseacrh), dengan membaca, menganalisis dan menyimpulkan literatur yang relevan. Ada dua model kepemimpinan yang Siti Walidah gunakan dalam membangun organisasi pendidikan, di antaranya adalah kepemimpinan transformasional, dan kepemimpinan visioner.